1982
DOI: 10.1530/jrf.0.0660537
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gonadotrophins on early follicle cell development and early oocyte growth in the immature rat

Abstract: Ovaries of neonatal rats were transplanted on the day after birth into ovariectomized (high gonadotrophin levels) or ovariectomized-hypophysectomized adult female rats (extremely low gonadotrophin levels). Although transplantation caused a reduction of the number of growing follicles in all transplants, it did not seem to induce a clearly abnormal course of follicle development. After 15 days of development, the hormone-rich transplants contained a greater number of follicles larger than type 4 and a smaller n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The number of follicles that start to grow per day in 16-day-old rats is reportedly higher than that in older rats [25]. Thus, previous reports indicate that the elevation of FSH during this time appears to be essential for normal follicular development in the neonatal rat and mouse [6][7][8]. The present data are in agreement with those of previous studies that reported elevated plasma FSH levels during the second to third week of postnatal life in the female rat.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The number of follicles that start to grow per day in 16-day-old rats is reportedly higher than that in older rats [25]. Thus, previous reports indicate that the elevation of FSH during this time appears to be essential for normal follicular development in the neonatal rat and mouse [6][7][8]. The present data are in agreement with those of previous studies that reported elevated plasma FSH levels during the second to third week of postnatal life in the female rat.…”
Section: Discussionsupporting
confidence: 92%
“…The primary follicles can be seen in the female rat ovary as early as PND 5, and they develop into preantral follicles by PND 12 [6]. The early rise in plasma FSH levels coincides with the appearance of these preantral follicles, with a few layers of granulosa cells; thus, the elevated plasma FSH level during this time frame has been implicated as being essential for normal follicular growth [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetical local factors from atretic [4,13] or growing follicles [2] have been proposed to affect the onset of follicular growth. Some investigators have maintained that gonadotropins regulate the onset of follicular growth [14,15]; others disagree [4,16]. It is useful in this context to distinguish between true "feedback regulation" (in which perturbation of the system is followed by a return to homeostasis) and mere "impact" (in which perturbation of the system alters the status quo but does not result in return to homeostasis).…”
Section: Discussionmentioning
confidence: 99%
“…But the present histological study revealed the presence of more atretic follicles in the ovary upon treatment with the above mentioned doses. Since gonadotropins were the regulator of follicular development (Nimrod et al, 1976;de Wolff-Exalto, 1982;Albertini and Wassarman, 1994) and steroid production in rats (Albertini and Wassarman, 1994), it was quite possible that subnormal levels of gonadotropins might have affected oocyte development and maturation, ovulation, and corpora lutea formation in rat (Terranova, 1981).…”
Section: Discussionmentioning
confidence: 99%